The effect of differences between house length and placement zones inside the closed house on the utilization of broiler chicken feed protein in the dry season - Arjanggi Ari Bimo; Teysar Adi Sarjana; Edjeng Suprijatna (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
The research aims to examine the effect of differences in house length and placement zones inside a closed house on the utilization of broiler chicken feed protein in the dry season. The research material is 600 broiler chickens (strain cobb) divided into 20 experimental units and 2 closed houses with a length of 60 m with a capacity of 11,000 and a length of 120 m with a capacity of 22,000. This research used a randomized block design with a split-plot pattern and two factors. The main plot is closed house with length 60 and 120 meters, the subplot is the zone placement of chicken which are divided into 4 zones: zone 1 is parallel to the inlet, zone 2 is measured at 1/4 of the house length, zone 3 is measured at 1/2 the house length, zone 4 is measured at 3/4 the house length from the inlet. The parameters observed were protein digestibility, the protein efficiency ratio (PER), and nitrogen retention (NR). Macroclimate, microclimate, and microclimatic ammonia observed as supporting data and an overview of the research conditions. Longer house and placement zone of chicken further from the inlet increase temperature, humidity, and microclimatic ammonia inside the closed house. The results showed an interaction between the house length and placement zone of chicken against NR. The housing length of 120 m and zone 4 was significantly (P≤0,05) having lower protein digestibility, PER, and NR values. Protein digestibility began to decrease significantly (P≤0,05) in zone 3, while PER and NR significantly decrease from zone 2. It concludes that longer closed house and placement zones further from the inlet decrease the ability of broilers to utilizing feed protein in the dry season.